2018
DOI: 10.1021/acs.energyfuels.8b02394
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hardness of Charcoal Varies According to the Final Temperature of Carbonization

Abstract: Hardness has been considered to be one of the most important mechanical indicators of material quality. Here, an automated portable hardness tester was used to evaluate dynamic hardness (DH) of vegetable charcoal for industrial application, correlating these results to vegetal material and final temperature of carbonization. Wood specimens from nine vegetal materials were pyrolysed at final temperatures of 300, 450, 600, and 750 °C. A total of 45 wood specimens were used as the sample control. DH of wood and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Nevertheless, the analyzed feedstocks have different bulk densities, which could also play a key role in determining the impact resistance and shear strength of HO-derived. This is in line with the results reported by Kumar et al [37] and de Abreu Neto et al [43], who observed a positive correlation between hardness and apparent density of wood chars. However, Dias Júnior et al [38], in view on their breaking strength measurements for several charcoals produced at different pyrolysis temperatures, suggested that the apparent density of charcoal by itself was not a suitable indicator of its mechanical resistance.…”
Section: Strength Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the analyzed feedstocks have different bulk densities, which could also play a key role in determining the impact resistance and shear strength of HO-derived. This is in line with the results reported by Kumar et al [37] and de Abreu Neto et al [43], who observed a positive correlation between hardness and apparent density of wood chars. However, Dias Júnior et al [38], in view on their breaking strength measurements for several charcoals produced at different pyrolysis temperatures, suggested that the apparent density of charcoal by itself was not a suitable indicator of its mechanical resistance.…”
Section: Strength Measurementssupporting
confidence: 93%
“…Morphological characterization was carried out for three samples (i.e., three different pyrolysis runs) of each type of biochar (or treatment). 10% in weight of the coarse fraction (>2 mm length) was sampled fragment (resulting in 368 and 172 fragments for VS and HO-derived biochars, respectively) and the following measures were performed: length and diameter (digital caliper Twin-Cal IP40, TESA, Renens, Switzerland), mass (precision balance cp224s-Oce, Sartorius, Goettingen, Germany), volume (by displacement of water in a graduate tube [43]), and bulk density of each individual fragment as a quotient between the two latter parameters. The shape coefficient was calculated as the quotient between the measured diameter of each fragment and the equivalent diameter (diameter of a cylinder with equivalent volume).…”
Section: Production Of Biochar and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lower SCF indicates a smaller volume of wood to be stored and transported in the industry and better use of the volume of carbonization kilns, reducing operational costs. In this study, even in the narrowest spacings, the SCF tends to be higher, which is probably related to the WBD they presented, since the WBD positively affects the CAD and its CGY, and denser wood would be consumed more slowly during pyrolysis [21,32] A signi cant effect of forking on SCF also occurred. Forked trees had higher SCF (6.0 of wood ton − 1 of charcoal) compared to the non-forked trees (5.5 m 3 of wood ton − 1 of charcoal) (Fig.…”
Section: The Speci C Consumption Of Rewood and Estimate Of Xed Carbon...mentioning
confidence: 57%
“…S1 (Supplementary material) shows the variation in FCP with basic density. Temperature stands out as the primary parameter in uencing carbonization yields [32,33], potentially elucidating why the CGY, PLY, NCGY, and FCY of T. vulgaris wood, subjected to identical heating rates and nal temperatures, exhibited no statistically signi cant differences.…”
Section: Gravimetric Yields Of the Pyrolysis Processmentioning
confidence: 99%